EpiNet study of incidence of status epilepticus in Auckland, New Zealand: Methods and preliminary results. (29th August 2018) - Bergin, Peter S.; Brockington, Alice; Jayabal, Jayaganth; Scott, Shona; Litchfield, Rhonda; Roberts, Lynair; Timog, Jerelyn; Beilharz, Erica; Dalziel, Stuart R.; Jones, Peter; Yates, Kim; Thornton, Vanessa; et al.
Summary: The EpiNet project has been commenced to facilitate investigator‐led collaborative research in epilepsy. A new Web‐based data collection tool has been developed within EpiNet to record comprehensive data regarding status epilepticus and has been used for a study of status epilepticus in Auckland, New Zealand. All patients aged >4 weeks who presented to any of the five public hospitals and the major private hospital within Auckland city (population = 1.61 million) with an episode of status epilepticus between April 6, 2015 and April 5, 2016 were identified using multiple overlapping sources of information. For this study, status epilepticus was defined as any seizure exceeding 10 minutes in duration, or repeated seizures lasting >10 minutes without recovery between seizures. Patients who had either convulsive or nonconvulsive status epilepticus were included. Episodes of status epilepticus were classified according to the 2015 International League Against Epilepsy ILAE status epilepticus classification. A total of 477 episodes in 367 patients were considered as definite or probable status epilepticus; 285 episodes (62%) lasted >30 minutes, which is the duration that has previously been used for epidemiological studies of status epilepticus.